EFFECT OF ORGANIC SOURCES OF NUTRIENTS ON SOIL PARAMETERS AND THEIR EFFECT ON THE INCIDENCE OF SUCKING PESTS - NAIK, M.I.; BASAVARAJ, K.; PRASANNA, S.O. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2013)
A field investigation on influence of soil amendments on the incidence of sucking pests in Bt cotton results revealed that there was no significant difference between the treatments with respect to soil pH. However, the organic carbon (%) was more in organic amendment treated treatment (PM+NC recorded 0.35, 0.35 and 0.36% at 30, 60 and 90 DAS. respectively). While, with respect to EC, organic amendments had both positive and negative role. The N, P and K content were on par between the treatments except untreated check. However highest amount of N. P and K was recorded in RDF and standard check which received the nitrogen, phosphorus and potash directly in to the soil. There was no significant difference between the treatments with respect to exchangeable calcium (ranges from 3.01 to 3.35 cinol(p4) kg 1)and magnesium (ranges from 0.95 to 1.31) at 30, 60 and 90DAS. Similar trend was found even with respect to sulphur content in the soil. This was ranged from 11.73 to 14.75ppm among the treatments compared to untreated check with 12.53. 12.21 and 1 I .73ppm sulphur content at 30, 60 and 90 DAS. respectively in the soil.